Mama's boy : a story from our Americas - Black, Dustin Lance (Alfred A. Knopf, 2019)
"From the Academy Award-winning screenwriter and political activist, a candid, vivid, powerfully resonant memoir about growing up as a gay Mormon in Texas that is, as well, a moving tribute to the mother who taught him about surviving against all odds Dustin Lance Black wrote the Oscar-winning screenplay for Milk and helped overturn California's anti-gay marriage Proposition 8, but as an LGBTQ+ activist he has unlikely origins. Raised in a military, Mormon household outside San Antonio, Texas, Black always found inspiration in his plucky, determined mother. Having contracted polio as a small girl, she endured leg braces and iron lungs, and was repeatedly told that she could never have children or live a normal life. Defying expectations, she raised Black and his two brothers, built a career, escaped two abusive husbands, and eventually moved the family to a new life in Southern California. While Black struggled to come to terms with his sexuality--something antithetical to his mother's religious views--she remained his source of strength and his guiding light. Later, she would stand by his side when he helped bring the historic gay marriage case to the U.S. Supreme Court. Mama's Boy is a stirring celebration of the connections between mother and son, Red states and Blue, and the spirit of optimism and perseverance that can create positive change in the world"--